PENGARUH PENANAMAN KAYU ULIN DAN KAYU GELAM DALAM MORTAR SEBAGAI BALOK STRUKTUR RUMAH KAYU SEDERHANA BERDASARKAN SIFAT FISIK DAN SIFAT MEKANIK - Fadhila Zulfa Mawaddah; Basyaruddin Basyaruddin (Rekayasa Sipil, 2021)
Timber demand is increasing, especially in the field of construction. In its use wood is not used just like that, but mixed or combined with other materials. Wood and mortar have different material properties which when they are combined, it will affect the strength, so the research is carried out by comparing the strength of wood before and after planting in the mortar based on physical and mechanical properties with the test standards referring to PKKI NI-5 1961, ASTM D2395-14, and ASTM D442-92. From the results of direct testing and previous studies which then carried out the numerical analysis, it is known that the strength of gelam wood and ironwood after being planted in mortar has increased, but not significantly.